Correlation of Clinical and Biochemical Parameters with the Stages of Chronic Kidney Disease in Type 2 DM Patients in a Tertiary Care Hospital in Chittagong (Journal of Chittagong Medical College Teachers' Association, 2022)
Background : Microalbuminuria is a term to describe a moderate increase in the level of urine albumin. It occurs when the kidney leaks small amounts of albumin into the urine. The main objective of this study is to determine the correlation between microalbuminuria and diabetic kidney disease at a tertiary care hospital in Chittagong.Materials and methods : Institutional based cross- sectional study design was conducted on randomly selected diabetic population from Chittagong Diabetic and General Hospital by using systematic random sampling  method from 1st June to 30th November 2019.Results : Out of a total of 160 participants, the prevalence  of microalbuminuria was in 59(36.9%) patients. Ten (6.3%) patients had cardiovascular disease, 18(11.3%) had neuropathy, 7(4.4%) had retinopathy, 117(73.1%) had hypertension and 47(29.4%) had duration of diabetes of 610 years. Majority 132(82.5%) patients had stage 1-2 followed by 22(13.8%) had stage 3, 4(2.5%) had stage 4 and 2(1.3%) had stage 5. Gender, age, cardiovascular, retinopathy, hypertension, BMI, albumin to creatinine ratio, fasting sugar, creatinine level and LDL were not statistically significant (p>0.05) when compared to different stages of CKD. Stage 1-2 was significantly higher in no microalbuminuria group than microalbuminuria group (92.1% vs 66.1%). Stage 3 was significantly higher in microalbuminuria group than no microalbuminuria group (23.7% vs 7.9%). Stage 4 was significantly higher in microalbuminuria group 4(6.8%) and Stage 5 was higher in the microalbuminuria group 2(3.4%).Conclusion: Neuropathy, mean diabetes duration, mean HbA1c, and mean Triglyceride were significantly greater in CKD stage 5 than in other stages of illness in the current research. When comparing different stages of CKD, mean HDL was considerably lower in stage 5. In the microalbuminuria group, CKD Stages 3, 4, and 5 were considerably higher than in the non-microalbuminuria group.JCMCTA 2022 ; 33 (1) : 50-55